Training Needs of Poultry Farmers in Hilly Areas - R. P. Sahu and N. K. Singh, (Indian Journal of Extension Education, 2014)
Temperature of brooder, time of removal of chick guard, type of brooding system, method of providing feed to thebrooding chicks, duration of heating brooder, house before chicks to brood, number of brooding days and purpose of chickguard, were perceived by the poultry farmers as more important training needs in brooding practices. While the aspectslike percentage of moisture to be maintained in litter, period of regular and slight hoeing of litter in a viable shed, thicknessof litter material to be added every month, replacement of litter from a viable poultry unit and basic qualities of the littermaterial were considered as more important training needs under litter management practices. The poultry farmersperceived that dose of fowl pox vaccine, age at which vaccination against fowl pox is done, dose of mareek's diseasevaccine, age at which vaccination against mareek's disease is done, medicine used to kill internal parasites and rate ofcoccidistat for mixing with feed were the more important training needs in vaccination practices. Whereas, under feedingpractices, source of vitamin in feed, source of protein in feed, source of minerals in feed and source of carbohydrates infeed were considered as more important training needs. Training assumes a special recognition in view of growingsophistication in poultry farming and allied technology. In order to make a training more meaningful and effective, thetraining needs of the poultry farmers have to be identified before implementing any training programme. The presentstudy was undertaken with the objective to assess the training needs of poultry farmers in Bageshwar district ofUttarakhand.